2019
DOI: 10.1093/brain/awz377
|View full text |Cite|
|
Sign up to set email alerts
|

Homozygous GRN mutations: new phenotypes and new insights into pathological and molecular mechanisms

Abstract: Homozygous mutations in the progranulin gene (GRN) are associated with neuronal ceroid lipofuscinosis 11 (CLN11), a rare lysosomal-storage disorder characterized by cerebellar ataxia, seizures, retinitis pigmentosa, and cognitive disorders, usually beginning between 13 and 25 years of age. This is a rare condition, previously reported in only four families. In contrast, heterozygous GRN mutations are a major cause of frontotemporal dementia associated with neuronal cytoplasmic TDP-43 inclusions. We identified … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 51 publications
2
57
1
Order By: Relevance
“…Our findings also provide insight into the function of PGRN. Recently, a potential role of PGRN in lysosome homeostasis has emerged based on the discovery that multiple cases of homozygous GRN mutation carriers develop neuronal ceroid lipofuscinosis-11 (CNL11), a lysosomal storage disease [4,18,50,105]. We, and other labs, have found that PGRN is trafficked to the lysosome and processed by cathepsins into granulins, which may be bioactive [47,68,133].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also provide insight into the function of PGRN. Recently, a potential role of PGRN in lysosome homeostasis has emerged based on the discovery that multiple cases of homozygous GRN mutation carriers develop neuronal ceroid lipofuscinosis-11 (CNL11), a lysosomal storage disease [4,18,50,105]. We, and other labs, have found that PGRN is trafficked to the lysosome and processed by cathepsins into granulins, which may be bioactive [47,68,133].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested novel functions of PGRN in lysosomes. Complete loss of PGRN leads to neuronal ceroid lipofuscinosis (NCL), a lysosomal storage disease (Smith et al, 2012;Almeida et al, 2016;Huin et al, 2020). Although primary trafficking pathways of PGRN are not completely clear, cell biologic studies demonstrated that PGRN can be either sorted intracellularly from ER/Golgi or taken up extracellularly and targeted to lysosomes through sortilin (Hu et al, 2010) and prosaposin (Zhou et al, 2015) pathways, where it undergoes proteolytic processing into stable granulin peptides (Holler et al, 2017;Lee et al, 2017;Zhou et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…In other neurodegenerative diseases, there is the strong association of heterozygous variants of PGN, the progranulin gene with fronto-temporal dementia and variants of GNPTAB, GNPTG, and the functionally related NAGPA gene with non-syndromic stuttering. Since homozygous or biallelic mutations of PGN are responsible respectively for neuronal ceroid lipofuscinosis type 11 and for the mucolipidosis subtypes, characterized by multiple lysosomal effects, dose effects of heterozygous gene variants in causation of diverse neuropsychiatric diseases is clearly established (Huin et al, 2020;Raza et al, 2016). The extent to which such rare variants directly account for mental illness is emerging from population-wide whole-genome sequencing data -a promising approach in national health initiatives to improve diagnosis (Walkley et al, 2010).…”
Section: Discussionmentioning
confidence: 99%